Influence of Inoculation with Bradyrhizobia and Nitrogen Rate on Yield and Estimated Economic Return of Virginia Market‐Type Peanut. Issue 1 (18th October 2018) - Jordan, David L.; Johnson, P. Dewayne; Hare, Andrew T.; Anco, Dan; Chapin, Jay; Thomas, James; Monfort, Scott; Balota, Maria
Abstract : Core Ideas: Bradyrhizobia inoculant increases peanut yield in new peanut fields and in fields with a recent history of peanut. Applied nitrogen is less effective than inoculation with Bradyrhizobia in new peanut fields. Return on investment from Bradyrhizobia inoculant occurs regardless of field history relative to peanut production. Adequate nitrogen (N) fixation by peanut ( Arachis hypogaea L.) is essential to optimize yield. In replicated trials in North Carolina, South Carolina, and Virginia from 1998–2017, commercially available in‐furrow liquid or granular inoculant increased yield from 3460 to 4660 lb/acre in new peanut fields (52 trials) and 4280 to 4450 lb/acre in fields with a previous history of peanut plantings within the past 4 years (43 trials). The increase in economic value from inoculation treatment ($8/acre) at a peanut price of $535/ton was $318/acre and $41/acre in fields with these respective histories. In a second experiment, replicated trials were conducted from 2007–2017 in fields without a history of peanut production or fields not rotated to peanut within at least the past 20 years. Economic return based on peanut prices described previously was determined to reflect cost of N applied as ammonium sulfate ($0.28/lb ammonium sulfate) as a single application 45 to 60 days after planting when canopy foliage began to express N deficiency. A linear or quadratic response to rates of 0, 60, 90, 120, and 150 lb N/acre was noted in five trials with no response observed in the remaining four trials. When these experiments were included with five other experiments where non‐inoculated and inoculated controls were compared with one rate only (120 lb N/acre), yield and economic return were greater for inoculated peanut compared with peanut receiving N or the non‐inoculated and non‐fertilized control. Nitrogen increased peanut yield and economic return compared with the non‐fertilized control. Results from these experiments underscore the value of inoculation with Bradyrhizobia at planting regardless of field history and the limitations of applied N to correct N deficiencies in peanut.